Technical aspects of flight safety of military aircraft - Čestić, Miroslav M.; Sokolović, Vlada S.; Dodić, Marjan D. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: The use of modern military aircraft requires an extraordinary effort of human and material potential to ensure the conditions for the execution of specific tasks. Complex technology, different spatial and temporal conditions of aircraft use impose the need to create organizational and technical conditions to assist the pilot during flight with the aim of safely and completely accomplishing the flight task. The aim of this paper is to identify possible problems in the organization of the flight safety system through the description of the influence of technical factors on flight safety and to find the best solutions for overcoming problems during the life cycle of the aircraft.Methods: In the research of the subject area, first of all, the analysis of the regulations regulating the field of flight safety was carried out, and then a description of the technical means and their impact on flight safety was carried out.Results: On the basis of the performed analysis, the activities to ensure the reliability of the aircraft during development and production were defined, and directions for improving flight safety were proposed through the amendments of regulations, organizational and technical as well as technological measures.Conclusion: The results of the analysis confirm the assumptions about the possible directions of development and improvement of flight safety of military aircraft through improvement and installation of technical systems (devices and equipment), both aviation and ground.
Keywords: flight safety; military aircraft; aircraft reliability